Faktor yang Berhubungan dengan Stres Kerja Pada Perawat Di Ruang Rawat Inap Rumah Sakit Ibnu Sina (YW-UMI) Makassar - Andi Batari Salsabila; Suharni A Fachrin; Mansur Sididi; Andi Mansur Sulolipu; Ayu Puspitasari (Window of Public Health Journal, 2026)
Job stress is one of the occupational health problems frequently experienced by healthcare workers, particularly nurses, and can impact performance, service quality, and patient safety. Hospitals should actively manage these factors to foster a supportive environment. Various factors related to work conditions are known to influence nurses' work stress levels. This study aims to determine the factors associated with work stress in nurses in the inpatient ward of Ibnu Sina Hospital (YW-UMI), Makassar. This study is a quantitative study with a cross-sectional study design. The study population was all nurses working in the inpatient ward of Ibnu Sina Hospital (YW-UMI), Makassar. The study sample consisted of 86 people selected using a total sampling technique. Data analysis was performed univariately and bivariately using the Chi-Square test with a 95% confidence level (α = 0.05). The results showed that workload (p = 0.002), work fatigue (p = 0.000), physical work environment (p = 0.000), and interpersonal communication (p = 0.000) were significantly associated with work stress among nurses in the inpatient ward of Ibnu Sina Hospital (YW-UMI), Makassar. This study concluded that workload, work fatigue, physical work environment, and interpersonal communication are factors associated with work stress among nurses. Therefore, hospitals need to regularly manage workload, control work fatigue, provide a comfortable work environment, and improve interpersonal communication to reduce the risk of work stress among nurses.